Human Bone Marrow Stromal Cells Differentiate into Corneal Tissue and Prevent Ocular Graft-Versus-Host Disease in Mice. Issue 12 (December 2015) - Sánchez-Abarca, Luis Ignacio; Hernández-Galilea, Emiliano; Lorenzo, Rebeca; Herrero, Carmen; Velasco, Almudena; Carrancio, Soraya; Caballero-Velázquez, Teresa; Rodríguez-Barbosa, José Ignacio; Parrilla, Marta; Del Cañizo, Consuelo; Miguel, Jesús San; Aijón, José; et al.
Clinical trials have assessed the use of human bone marrow stromal cells (hBMSCs) for the treatment of immune-related disorders such as graft-versus-host disease (GVHD). In the current study, we show that GFP + -transduced hBMSCs generated from bone marrow migrate and differentiate into corneal tissue after subconjunctival injection in mice. Interestingly, these hBMSCs display morphological features of epithelial, stromal, and endothelial cells and appear at different layers and with different morphologies depending on their position within the epithelium. Furthermore, these cells display ultrastructural properties, such as bundles of intermediate filaments, interdigitations, and desmosomes with GFP - cells, which confirms their differentiation into corneal tissues. GFP + -transduced hBMSCs were injected at different time points into the right eye of lethally irradiated mice undergoing bone marrow transplantation, which developed ocular GVHD (oGVHD). Remarkably, hBMSCs massively migrate to corneal tissues after subconjunctival injection. Both macroscopic and histopathological examination showed minimal or no evidence of GVHD in the right eye, while the left eye, where no hBMSCs were injected, displayed features of GVHD. Thus, in the current study, we confirm that hBMSCs may induce their therapeutic effect at least in part by differentiation and regeneration of damaged tissues in the host. Our results provide experimental evidence that hBMSCs represent a potential cellular therapy to attenuate oGVHD.